2020
DOI: 10.3389/fphar.2020.00668
|View full text |Cite|
|
Sign up to set email alerts
|

USP5 Promotes Metastasis in Non-Small Cell Lung Cancer by Inducing Epithelial-Mesenchymal Transition via Wnt/β-Catenin Pathway

Abstract: Ubiquitin-specific protease 5 (USP5) is a deubiquitinating enzyme that functions as an oncoprotein in a variety of human cancers. However, the expression and role of USP5 in the metastasis of non-small cell lung cancer (NSCLC) have not been addressed. In this study, we examined the expression and prognostic significance of USP5 in NSCLC. The results revealed that USP5 was overexpressed and correlated with metastasis and overall survival in NSCLC tissues. A further in vitro study revealed that the levels of USP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 33 publications
(36 reference statements)
0
26
0
Order By: Relevance
“…It is well known that dysregulated proliferation and metastasis are hallmarks of cancer cells (33,34), which is accountable for malignant features and poor prognosis of cancer patients. USP5 has been found to promote the epithelial-mesenchymal transition (EMT) and metastasis in NSCLC cells (35). Our cell model data together with Xue's data (35) have clarified that USP5 promotes the proliferation and metastatic malignant biological behaviors of NSCLC cells, thus providing a plausible explanation for the contribution of high level of USP5 to poor prognosis of NSCLC.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…It is well known that dysregulated proliferation and metastasis are hallmarks of cancer cells (33,34), which is accountable for malignant features and poor prognosis of cancer patients. USP5 has been found to promote the epithelial-mesenchymal transition (EMT) and metastasis in NSCLC cells (35). Our cell model data together with Xue's data (35) have clarified that USP5 promotes the proliferation and metastatic malignant biological behaviors of NSCLC cells, thus providing a plausible explanation for the contribution of high level of USP5 to poor prognosis of NSCLC.…”
Section: Discussionmentioning
confidence: 51%
“…Nonetheless, our data showed that genetic manipulation of USP5 alone could modulate the CCND1 protein level in NSCLC cells in which USP22 was highly expressed, indicating that two members of the USP family, USP5 and USP22, can exert an additional effect in the stabilization of CCND1 via similar or distinct mechanisms. Previous studies have also found that upregulating USP5 facilitates the proliferation, EMT, and metastasis of NSCLC cells through the stabilization of β-catenin (23) and the activation of β-catenin signaling (23,35). It is well known that the transcription of CCND1, a classic downstream target of β-catenin, can be induced by the Wnt-β-catenin signaling pathway (46,47).…”
Section: Discussionmentioning
confidence: 98%
“…Active β-Catenin signaling depends on its nuclear translocation and is strongly linked with EMT processes and aerobic glycolysis in different cancers ( Cai et al, 2018 ; Fang et al, 2019 ; Zuo et al, 2020 ). In CRC, dysregulated β-Catenin signaling participates in the regulation of tumor invasion, metastasis formation and aerobic metabolism, and various mutations in crucial regulatory factors of the Wnt/β-Catenin pathway have already been widely noted in CRC ( Jiao et al, 2020 ; Wang et al, 2020 ; Xue et al, 2020 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…USP5, also named as isopeptidase T (IsoT), belongs to peptidase C19 family and prefer to cleave unanchored polyubiquitin chains [ 27 ], thus, it is crucial for free ubiquitin recycling. Besides its ubiquitin recycling function, USP5 is able to remove polyubiquitin chain on protein substrates and several proteins has been identified as USP5 substrates including FoxM1, c-Maf, and β-catenin [ 28 31 ]. It has been reported that knockdown of USP5 resulted in accumulation of unanchored polyubiquitin and activation of p53 pathway [ 32 ].…”
Section: Discussionmentioning
confidence: 99%